Comparative study on metal biosorption by two macroalgae in saline waters: single and ternary systems - Figueira, Paula (2016)
The biosorption capability of two marine macroalgae (green Ulva lactuca and brown Fucus vesiculosus) was evaluated in the removal of toxic metals (Hg, Cd and Pb) from saline waters, under realistic conditions. Results showed that, independently of the contamination scenario tested, both macroalgae have a remarkable capacity to biosorb Hg and Pb. In single-contaminant systems, by using only c.a. 500 mg of non-pre-treated algae biomass (size <200 μm) per litter, it was possible to achieve removal efficiencies between 96 and 99 % for Hg and up to 86 % for Pb. Despite the higher removal of Hg, equilibrium was reached more quickly for Pb (after 8 h). In multi-contaminant systems, macroalgae exhibited a similar selectivity toward the target metals: Hg > Pb> > Cd, although Pb removal by U. lactuca was more inhibited than that achieved by F. vesiculosus. Under the experimental conditions used, none of the macroalgae was effective to remove Cd (maximum removal of 20 %). In all cases, the kinetics of biosorption was mathematically described with success. Globally, it became clear that the studied macroalgae may be part of simple, efficient, and cost-effective water treatment technologies. Nevertheless, Fucus vesiculosus has greater potential, since it always presented higher initial sorption rates and higher removal efficiencies.